Moving to VB .NET: Strategies, Concepts, and Code, Second Edition - Appleman, Daniel (Apress, 2012)
Microsoft’s .NET Framework is the most significant change to Windows since the transition from DOS. It’s not surprising that even though it has been available for over a year, and is now in its second ( Visual Studio 2003) edition, many VB6 developers have been slow to adopt it. In fact, large numbers of Visual Basic developers have done little more than read articles about it in magazines or perhaps read promotional material from Microsoft. Many have just begun to start experimenting with it and creating their own applications.